Comparison of efficacy and effectiveness between ULTRACETTM and Tramadol/Acetaminophen in acute postoperative pain after upper extremity surgery - Passakorn Sawaddiruk (2018)
Objective: To compare the efficacy and effectiveness between ULTRACETTM, a new analgesic combination of tramadol/ acetaminophen, and tramadol/acetaminophen for acute postoperative pain after upper extremity surgery. Study design: A double blind randomized controlled trial. Material and Method: One hundred and eighty patients who underwent upper extremity surgery under brachial plexus block were randomized to receive either ULTRACETTM (n = 87) or tramadol and acetaminophen (n = 93) immediately after surgery in the postanesthetic care unit (PACU). Total morphine requirement, pain score (VRS) and drug adverse effects were compared between those two groups using independent single t-test, Mann-Whitney U-test, Chi-square test and Fisher-exact test respectively. Results: Total morphine requirement was significantly lower in subjects who used ULTRACETTM when compared with the tramadol and acetaminophen group (0.51 and 0.69 mg in the first 6 hours after the operation, 0.0 and 0.13 mg in hours 6-12 after the operation). Moreover, there were fewer side effects in this ULTRACETTM group too. Conclusion: ULTRACETTM has more efficacy and fewer side effects when compared with tramadol and acetaminophen in acute postoperative pain surgery.